1984
DOI: 10.1002/bit.260260502
|View full text |Cite
|
Sign up to set email alerts
|

Purification and some properties of pure Cochliobolus lunatus fibrinolytic Enzyme

Abstract: Purification of partially purified fibrinolytic enzyme was attempted by chromatography on DEAE-cellulose (D-52) column. The results indicated the resolution of three protein components and one minor component. It was shown that the first component was the major of the applied sample. Examination of fibrinolytic activity of the different fractions of components one and two indicated that only the first component possessed fibrinolytic activity. Fibrinolytic activity of the applied sample was completely recovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…It should be noted that because of the SPR characteristic, metallic silver nanocrystals indicated an optical absorption peak at roughly 3 keV. [9] Finally, the AFM 2D and 3D topographical images of synthesized AgNPs are shown in Figure 3F (a and b), respectively. It is clear from AFM images that AgNPs exhibited a uniform particle distribution and spherical shape with an average diameter around 30 nm.…”
Section: Gram-positive Bacteriamentioning
confidence: 92%
See 3 more Smart Citations
“…It should be noted that because of the SPR characteristic, metallic silver nanocrystals indicated an optical absorption peak at roughly 3 keV. [9] Finally, the AFM 2D and 3D topographical images of synthesized AgNPs are shown in Figure 3F (a and b), respectively. It is clear from AFM images that AgNPs exhibited a uniform particle distribution and spherical shape with an average diameter around 30 nm.…”
Section: Gram-positive Bacteriamentioning
confidence: 92%
“…Previously, many researchers have revealed that herbal nanoparticles similar to herbal extracts do not exhibit cytotoxicity properties. [9,10]…”
Section: Evaluation Of Cytotoxicity Effect Of Agnps@ziziphoramentioning
confidence: 99%
See 2 more Smart Citations
“…They have combined nanotechnology with medicine to synthesize such supplements. [16] Among the metallic nanoparticles, the place of gold nanoparticles synthesized by plants is very special. Bioreduction of AuNPs is obtained via either plant tissues or microorganisms.…”
Section: Introductionmentioning
confidence: 99%